Effects of Chinese Propolis in Protecting Bovine Mammary Epithelial Cells against Mastitis Pathogens-Induced Cell Damage - Kai Wang; Xiao-Lu Jin; Xiao-Ge Shen; Li-Ping Sun; Li-Ming Wu; Jiang-Qin Wei; Maria Cristina Marcucci; Fu-Liang Hu; Jian-Xin Liu (Mediators of Inflammation)
Chinese propolis (CP), an important hive product, can alleviate inflammatory responses. However, little is known regarding the potential of propolis treatment for mastitis control. To investigate the anti-inflammatory effects of CP on bovine mammary epithelial cells (MAC-T), we used a range of pathogens to induce cellular inflammatory damage. Cell viability was determined and expressions of inflammatory/antioxidant genes were measured. Using a cell-based reporter assay system, we evaluated CP and its primary constituents on the NF-κB and Nrf2-ARE transcription activation. MAC-T cells treated with bacterial endotoxin (lipopolysaccharide, LPS), heat-inactivated Escherichia coli, and Staphylococcus aureus exhibited significant decreases in cell viability while TNF-α and lipoteichoic acid (LTA) did not. Pretreatment with CP prevented losses in cell viability associated with the addition of killed bacteria or bacterial endotoxins. There were also corresponding decreases in expressions of proinflammatory IL-6 and TNF-α mRNA. Compared with the mastitis challenged cells, enhanced expressions of antioxidant genes HO-1, Txnrd-1, and GCLM were observed in CP-treated cells. CP and its polyphenolic active components (primarily caffeic acid phenethyl ester and quercetin) had strong inhibitive effects against NF-κB activation and increased the transcriptional activity of Nrf2-ARE. These findings suggest that propolis may be valuable in the control of bovine mastitis.